2010
DOI: 10.1097/rct.0b013e3181bbf173
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Angiography and Digital Subtraction Angiography Findings in Popliteal Artery Entrapment Syndrome

Abstract: Computed tomographic angiography can demonstrate both the vascular changes and the anatomic variations in the popliteal fossa and may be valuable in the diagnosis of PAES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The duration of symptoms before diagnosis was reported in 10 of 30 PAES studies and was a median of 12 months (range, 4 hours-120 months). 24,29,30,33,35,37,39,44,48,50 No relationship between duration of symptoms and presence of irreversible arterial damage (occlusion, poststenotic dilatation, or aneurysm formation) was found in the three studies that reported sufficient patient-level detail to carry out this analysis (P ϭ .55, P ϭ .17, and P ϭ .64, two-sided Mann-Whitney U test). 24,30,48 Surgical treatments.…”
Section: Articles Retrieved From Electronic Search N=291mentioning
confidence: 66%
See 3 more Smart Citations
“…The duration of symptoms before diagnosis was reported in 10 of 30 PAES studies and was a median of 12 months (range, 4 hours-120 months). 24,29,30,33,35,37,39,44,48,50 No relationship between duration of symptoms and presence of irreversible arterial damage (occlusion, poststenotic dilatation, or aneurysm formation) was found in the three studies that reported sufficient patient-level detail to carry out this analysis (P ϭ .55, P ϭ .17, and P ϭ .64, two-sided Mann-Whitney U test). 24,30,48 Surgical treatments.…”
Section: Articles Retrieved From Electronic Search N=291mentioning
confidence: 66%
“…[52][53][54][55] By using surgical confirmation of pathology as the reference standard and provocation catheter arteriography as the index test, 13 of 21 studies provided sufficient information to yield a mean estimate of sensitivity for provocation arteriography of 97% (median, 100%; range, 85%-100%). [22][23][24]27,30,33,36,37,39,40,[42][43][44] Similar estimates for other diagnostic modalities are given in Table II. One prospective study and five of seven retrospective case series on PAES recommended the use of cross-sectional magnetic resonance (MR) imaging (MRI)/MR angiography (MRA) or computed tomography (CT)/CT angiography in diagnosis because it allowed visualization of the common vas- cular (arterial stenosis, occlusion, aneurysmal change, and deviated course) and extravascular (abnormal muscle attachments and muscular hypertrophy) anatomic abnormalities implicated in arterial entrapment.…”
Section: Articles Retrieved From Electronic Search N=291mentioning
confidence: 85%
See 2 more Smart Citations
“…Multiplanar reconstruction, maximum intensity projection, and volume rendering are valuable tools for the surgeon's preoperative planning. 15 At Walter Reed, the CT scanner is a GE Healthcare Lightspeed device (General Electric, Milwaukee, WI). Using a Stellant dual-head injector (Medrad, Warrendale, PA), we inject 90-140 mL of intravenous contrast into the antecubital fossa, followed by 50 mL of normal saline.…”
Section: Discussionmentioning
confidence: 99%